Polscy jezuici na ziemiach greckich od XVI do XX wieku - Homa, Krzysztof (Annales Missiologici Posnanienses, 2021)
The main purpose of this article is to provide some information about missionary work of Polish Jesuits in Greece and in Constantinople from XVI to XX century. It was the period of Turkokratia and later of Independent Greece. Article is divided into four small chapters. After a general introduction to the topic, the first chapter “Constantinople” is giving us some information about 18 Jesuits, who worked in Constantinople from XVI until XIX century. Second chapter presented Polish Jesuits who worked on Islands of Aegean Sea: Syros, Tinos, Chios in the XIX century, especially Fathers: Tadeusz Kuczyński, Dominik Osmołowski and Józef Skulina. Third chapter is about Jesuits traveling and working temporarily in Greece in XIX century and in the beginning of XX century, especially Fathers: Maksymilian Ryłło and Marcin Czermiński. Last chapter presented some Jesuits working in Athens in the XX century. Article finished with bibliography and information about Polonica in the Jesuit Archive in Athens. It is not very deep research but rather a kind of signal showing new topics for historic, scientific work.